Proceedings of the 19th International Conference on Supporting Group Work 2016
DOI: 10.1145/2957276.2957313
|View full text |Cite
|
Sign up to set email alerts
|

Habits of the Heart(rate)

Abstract: We investigate interpretations of a biosignal (heartrate) in uncertain social interactions. We describe the quantitative and qualitative results of a randomized vignette experiment in which subjects were asked to make assessments about an acquaintance based on an imagined scenario that included shared heartrate information. We compare the results of this experiment in adversarial and non-adversarial contexts of interaction. We find that elevated heartrate transmits cues about mood in both contexts, but that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In order to manipulate the presence of biosignal information we included two biosignal information conditions, one with (HR Graph) and one without a visual (HR Caption). Heart rate information is known to be ambiguous and can be interpreted in various ways [53]. In fact, in our preliminary pilots, many participants cited withdrawal as a cause for the changes in Jared's heart rate.…”
Section: Methodsmentioning
confidence: 93%
“…In order to manipulate the presence of biosignal information we included two biosignal information conditions, one with (HR Graph) and one without a visual (HR Caption). Heart rate information is known to be ambiguous and can be interpreted in various ways [53]. In fact, in our preliminary pilots, many participants cited withdrawal as a cause for the changes in Jared's heart rate.…”
Section: Methodsmentioning
confidence: 93%
“…Nevertheless, people seem to attribute emotional information to heart rate data, including information about the subject's emotional valence. One study found that in uncertain social situations, elevated heart rate was perceived to be related to negative mood [6]. Surprisingly, the same study found that normal, but not elevated, heart rate influenced trustworthiness negatively in an adversarial condition.…”
Section: Physio-social Mediamentioning
confidence: 96%
“…Heart-rate sharing has been proposed as a way to provide implicit emotional information in CMC [3,4,[6][7][8][9][10][11]. Furthermore, other types of physiological data have been explored previously, for example brain waves [34], skin conductance [5,35] and synchronization of biosignals [36].…”
Section: Physio-social Mediamentioning
confidence: 99%
See 2 more Smart Citations